Oxylipin Responses to Fasting and Insulin Infusion in a Large Mammalian Model of Fasting-Induced Insulin Resistance, the Northern Elephant Seal - Michael La Frano (9987986); Rudy Ortiz (7456632); John W. Newman (9988001) (2021)
This study complements the previous study by examining the effects of fasting duration and insulin infusion on circulating levels of oxylipins, bioactive metabolites derived from the oxygenation of polyunsaturated fatty acids. Northern elephant seal pups were studied at two post-weaning periods (n = 5/period): early fasting (1–2 weeks post-weaning; 127 ± 1 kg) and late fasting (6–7 weeks post-weaning; 93 ± 4 kg). Different cohorts of pups were weighed, sedated, and infused with 65 mU/kg of insulin. Plasma was collected prior to infusion (T0), and at 10, 30, 60, and 120 min post-infusion. A profile of ~80 oxylipins were analyzed by UPLC-ESI-MS/MS.